2017
DOI: 10.1007/s00394-017-1566-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between egg consumption and cardiovascular disease events, diabetes and all-cause mortality

Abstract: PurposeThe association between egg consumption and cardiovascular disease (CVD) or type 2 diabetes (T2D) remains controversial. We investigated the association between egg consumption and risk of CVD (primary outcome), T2D and mortality in the Caerphilly prospective cohort study (CAPS) and National Diet and Nutritional Survey (NDNS).MethodsCAPS included 2512 men aged 45–59 years (1979–1983). Dietary intake, disease incidence and mortality were updated at 5-year intervals. NDNS included 754 adults aged 19–64 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 34 publications
2
47
2
2
Order By: Relevance
“…We screened a total of 763 studies, and 27 studies (28 including the current study) met inclusion criteria (supplemental fig 4) 56891011124546474850515253545556575859606162636465. Supplemental table 10 presents characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We screened a total of 763 studies, and 27 studies (28 including the current study) met inclusion criteria (supplemental fig 4) 56891011124546474850515253545556575859606162636465. Supplemental table 10 presents characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…In studies with only dose-response estimates, we calculated the relative risk for one egg per day and used this estimate in the meta-analysis of high versus low egg consumption. For studies that did not publish person years for each category of egg intake,68945464748 we imputed person years based on available data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings about the effects of egg consumption on fasting blood glucose levels have been mixed. While some studies have reported higher egg consumption to be associated with higher blood glucose in people with impaired glucose tolerance [ 36 ], other research shows that egg consumption can improve blood glucose levels in people with pre-diabetes and type II diabetes [ 37 , 38 ]. The current study found that egg consumption did not negatively affect fasting blood glucose in people with MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous prospective studies have examined the direct relation between DC intake and T2DM or IFG. Most frequently, eggs have been used as a surrogate for dietary cholesterol intake and the effects on diabetes risk have been variable, with some studies suggesting an adverse effect and others finding eggs to be inversely associated with T2DM risk [ 12 , 15 , 24 , 25 , 26 , 27 ]. A recent review concluded that any apparent adverse effect of egg consumption on either CVD or diabetes risk was most likely due to confounding by other dietary factors [ 28 ].…”
Section: Discussionmentioning
confidence: 99%